Incorporation of textile artificial magnetic conductor into dipole antenna - Abdullah, Muhammad Azfar (2014)
The radiation and gain characteristics of wearable dipole antenna which are omni-radiation pattern and low gain are not sufficient to support the wearable onbody system. So, to overcome these problems, the incorporation of textile dipole antenna with Artificial Magnetic Conductor (AMC) are designed and analysed. The purpose of implementing the dipole antenna with AMC is to reduce the antenna backward radiation towards the human body and to increase the antenna’s gain. By implementing this concept, the dipole antenna’s beam direction is shifted outward from the human body and the antenna’s gain is increased. In this thesis, the dipole antenna with AMC is investigated and analysed. The antenna's substrate is made of denim jeans. It has er = 1.7, tan s = 0.025 and 1mm thickness. The radiating materials are made of two different conducting fabrics which are Shieldit Super fabric and copper fabric. A flexible dipole antenna with 3 by 3 arrays flexible AMC, operating at 2.4GHz is designed. In order to have better performance of the integrated antennas, the properties of the fabric such as bending effect, wetness effect and on-body measurement are investigated. The possibility of different positions of the dipole antenna above the AMC which may alter the performance of the antenna is also discussed. Computer Simulation Technology (CST) software is used for the antenna and AMC simulation. The performances of the dipole antenna with and without AMC are compared. It shows that the performance of the antenna with AMC increases the gain by 5 dB and the antenna’s radiation is more directive. Furthermore, the resonant frequency of the antenna with AMC shifted due to the bending effect. The best location to put the dipole antenna with AMC is at the back of the human body.